The response of gene expression associated with lipid metabolism, fat deposition and fatty acid profile in the longissimus dorsi muscle of Gannan yaks to different energy levels of diets. - Chao Yang; Jianbin Liu; Xiaoyun Wu; Pengjia Bao; Ruijun Long; Xian Guo; Xuezhi Ding; Ping Yan (PLoS ONE, 2017)
The energy available from the diet, which affects fat deposition in vivo, is a major factor in the expression of genes regulating fat deposition in the longissimus dorsi muscle. Providing high-energy diets to yaks might increase intramuscular fat deposition and fatty acid concentrations under a traditional grazing system in cold seasons. A total of fifteen adult castrated male yaks with an initial body weight 274.3 ± 3.14 kg were analyzed for intramuscular adipose deposition and fatty acid composition. The animals were divided into three groups and fed low-energy (LE: 5.5 MJ/kg), medium-energy (ME: 6.2 MJ/kg) and high-energy (HE: 6.9 MJ/kg) diets, respectively. All animals were fed ad libitum twice daily at 08:00-09:00 am and 17:00-18:00 pm and with free access to water for 74 days, including a 14-d period to adapt to the diets and the environment. Intramuscular fat (IMF) content, fatty acid profile and mRNA levels of genes involved in fatty acid synthesis were determined. The energy levels of the diets significantly (P<0.05) affected the content of IMF, total SFA, total MUFA and total PUFA. C16:0, C18:0 and C18:1n9c account for a large proportion of total fatty acids. Relative expression of acetyl-CoA carboxylase (ACACA), fatty acid synthase (FASN), stearoyl-CoA desaturase (SCD), sterol regulatory element-binding protein-1c (SREBP-1c), peroxisome proliferator-activated receptor γ (PPARγ) and fatty acid-binding protein 4 (FABP4) was greater in HE than in LE yaks (P<0.05). Moreover, ME yaks had higher (P<0.05) mRNA expression levels of PPARγ, ACACA, FASN, SCD and FABP4 than did the LE yaks. The results demonstrate that the higher energy level of the diets increased IMF deposition and fatty acid content as well as increased intramuscular lipogenic gene expression during the experimental period.